Motor endplate‐expressing cartilage‐muscle implants for reconstruction of a denervated hemilarynx. (12th December 2018) - Brookes, Sarah; Voytik‐Harbin, Sherry; Zhang, Hongji; Zhang, Lujuan; Halum, Stacey
Abstract : Objective: Tissue engineering of the larynx requires a complex, multiple tissue layer design. Additionally, spontaneous reinnervation of the larynx after recurrent laryngeal nerve (RLN) injury is often disorganized, resulting in subpar function. This study investigates use of tissue‐engineered cartilage and motor endplate‐expressing (MEE) tissue‐engineered skeletal muscle implants for laryngeal reconstruction and the promotion of organized reinnervation after RLN injury. Methods: F344 rat primary muscle progenitor cells (MPCs) were isolated. Three‐dimensional muscle constructs were created by encapsulating MPCs in type I oligomeric collagen under passive tension. Constructs were then cultured in differentiation medium (MPC control constructs) or induced to form motor endplates (MEE constructs) with neurotrophic agents. Three‐dimensional cartilage constructs were created with adipose stem cells differentiated in chondrocyte medium. The muscle and cartilage constructs were implanted into surgically created myochondral defects in the F344 rat larynx with injured or intact (control) RLN. At 1‐, 3‐, and 6‐month timepoints, videolaryngoscopy, electromyography (EMG), histology, and immunohistochemistry were used to assess outcomes. Results: At all timepoints, cartilage‐muscle implants were well integrated into host tissue. Functionally, there was increased vocal fold adduction and EMG activity in nerve‐injured rats treated with the MEE constructs when compared to those treated with the MPC control constructs. Motor endplate‐expressing constructs had increased myofiber cross‐sectional area compared to MPC control constructs. Conclusion: Although our laboratory previously demonstrated that muscle and cartilage constructs could be used separately for hemilaryngeal reconstruction, this study suggests combining them with the modification of MEEs rather than MPCs, resulting in improved muscle recovery after recurrent laryngeal nerve injury. Level of Evidence: NA Laryngoscope, 129:1293–1300, 2019